Management of Unruptured Small Multiple Intracranial Aneurysms in China: A Comparative Effectiveness Analysis Based on Real-World Data - Chen, Jigang; Tong, Xin; Feng, Xin; Peng, Fei; Niu, Hao; Han, Mingyang; Liu, Lang; Zhao, Yuanli; Wang, Daming; Pan, Yuesong; Liu, Aihua (Frontiers in Neurology, 2022)
Background: Unruptured small aneurysms with a size of less than 7 mm were often followed conservatively. However, it’s unknown whether unruptured small Multiple intracranial aneurysms (MIAs) are better to be prophylactically treated or conservatively followed. Objective: We aim to compare the effectiveness of different strategies regarding their management. Methods: A decision-analytic Markov model was built over a life span. The compared strategies include natural history, treat one aneurysm, treat both aneurysms, annual follow-up, biennial follow-up, and follow-up every 5 years. The inputs for the model were obtained from real-world data and related medical literature. Outcomes were measured in terms of quality-adjusted life-years (QALYs). Results: Treat both aneurysms had the highest effectiveness of 15.36 QALYs and treat one aneurysm had the second-highest effectiveness of 15.11 QALYs. Probabilistic sensitivity analysis with 10000 iterations showed that treat both aneurysms and treat one aneurysm was optimal in 67.28 % and 17.91% of all cases, respectively. One-way and two-way sensitivity analyses showed that the result was sensitive to the proportion of moderate to severe disability after treating two aneurysms, mortality after treating two aneurysms, the proportion of moderate to severe disability after treating one aneurysm, and the rupture rate of small growing aneurysm. Either treat both aneurysms or treat one aneurysm would be the optimal strategy under most of the circumstances with the variations of these parameters. Conclusion: For patients with small unruptured MIAs, prophylactic coiling was superior to conservative management and at least one aneurysm should be treated.